Macroeconomics and Drug Use: A Review of the Literature and Hypotheses for Future Research - Ellis-Griffith, Gregory (2016)
Despite more than a century of drug prohibition, problems of addiction and drug abuse continue to be major global public health and criminal justice concerns (United Nations Office on Drugs and Crime, 2015). It has long been obvious that many of these problems are entwined with other economic and social issues. The editors of The Economist, in reporting evidence of a decline in drug use in the UK, speculated on the impact of the concurrent economic slowdown and commented that, "few academics have studied the link between drug use and macroeconomic performance, and what work exists is inconclusive" (Drug use and abuse: The fire next time, 2011). The goal of this paper will be to examine the work that exists on this topic and to propose a set of hypotheses to be tested in future studies